2020
DOI: 10.3390/agriculture10120653
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Digital Agriculture: Adoption of Technologies and Perception of Brazilian Farmers

Abstract: The rapid population growth has driven the demand for more food, fiber, energy, and water, which is associated to an increase in the need to use natural resources in a more sustainable way. The use of precision agriculture machinery and equipment since the 1990s has provided important productive gains and maximized the use of agricultural inputs. The growing connectivity in the rural environment, in addition to its greater integration with data from sensor systems, remote sensors, equipment, and smartphones ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 39 publications
1
96
0
6
Order By: Relevance
“…Third, several studies focusing technology adoption have found that despite the significance of technology in improving productivity, unwillingness on the part of farmers to adopt could be a constraint to adoption [7,31]. This could be due to poor awareness, lack of insurance to manage the risks involved in up taking a new idea or lack of skills and knowledge about the appropriateness of technology, as reported by a study conducted in Brazil [59]. Lack of acceptance of technology has also been reported as a barrier to the adoption of agriculture 4.0 technologies in a HIC context [11].…”
Section: Reasons For Cautionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, several studies focusing technology adoption have found that despite the significance of technology in improving productivity, unwillingness on the part of farmers to adopt could be a constraint to adoption [7,31]. This could be due to poor awareness, lack of insurance to manage the risks involved in up taking a new idea or lack of skills and knowledge about the appropriateness of technology, as reported by a study conducted in Brazil [59]. Lack of acceptance of technology has also been reported as a barrier to the adoption of agriculture 4.0 technologies in a HIC context [11].…”
Section: Reasons For Cautionmentioning
confidence: 99%
“…A study on the perception of Brazilian farmers regarding the adoption of agriculture 4.0 technologies such as precision agriculture integrated with data from remote sensors on smartphones found that the cost of the machines, software, equipment and connectivity was a constraint to adoption [59]. More generally, capital availability has also been found to be a pre-requisite to the adoption of conservation agriculture technologies, especially where new equipment is needed [60].…”
Section: Finance and Capital For Investment Research And Developmentmentioning
confidence: 99%
“…Government investments, export volume, agricultural and consumer culture are also factors that directly impact the way food is grown, and the efforts and investments dedicated to production. Developed and emerging countries have different types of government investment for agricultural production and some are developing projects aimed at the digital transformation of agriculture in countries like China [158], Brazil [159], Mexico [160], Thailand [161,162] and others.…”
Section: Main Challengesmentioning
confidence: 99%
“…So, soil analysis is the only method that allows, before planting, to recommend adequate amounts of correctives and fertilizers to increase crop productivity and, as a consequence, crop production and profitability. Soil science is considered a strategic research topic for precision agriculture and smart farms [6,7].…”
Section: Introductionmentioning
confidence: 99%